miR-150 influences B-cell receptor signaling in chronic lymphocytic leukemia by regulating expression of GAB1 and FOXP1 - Mraz, Marek; Chen, Liguang; Rassenti, Laura Z; Ghia, Emanuela M; Li, Hongying; Jepsen, Kristen; Smith, Erin N; Messer, Karen; Frazer, Kelly A; Kipps, Thomas J (Blood, 2014)
We examined the microRNAs (miRNAs) expressed in chronic lymphocytic leukemia (CLL) and identified miR-150 as the most abundant, but with leukemia cell expression levels that varied among patients. CLL cells that expressed ζ-chain-associated protein of 70 kDa (ZAP-70) or that used unmutated immunoglobulin heavy chain variable (IGHV) genes, each had a median expression level of miR-150 that was significantly lower than that of ZAP-70-negative CLL cells or those that used mutated IGHV genes. In samples stratified for expression of miR-150, CLL cells with low-level miR-150 expressed relatively higher levels of forkhead box P1 (FOXP1) and GRB2-associated binding protein 1 (GAB1), genes with 3' untranslated regions having evolutionary-conserved binding sites for miR-150. High-level expression of miR-150 could repress expression of these genes, which encode proteins that enhance B-cell receptor signaling, a putative CLL-growth/survival signal. Also, high-level expression of miR-150 was a significant independent predictor of longer treatment-free survival or overall survival, whereas an inverse association was observed for high-level expression of GAB1 or FOXP1 for overall survival. This study demonstrates that expression of miR-150 can influence the relative expression of GAB1 and FOXP1 and the signaling potential of the B-cell receptor, thereby possibly accounting for the noted association of expression of miR-150 and disease outcome.
Keywords: senioři; Gene Expression Regulation, Leukemic; signální transdukce; transfekce; mikro RNA; represorové proteiny; adaptorové proteiny signální transdukční; Middle Aged; mužské pohlaví; forkhead transkripční faktory; Signal Transduction; Adult; Repressor Proteins; MicroRNAs; chronická lymfatická leukemie; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; ženské pohlaví; Forkhead Transcription Factors; Adaptor Proteins, Signal Transducing; Humans; Leukemia, Lymphocytic, Chronic, B-Cell; receptory antigenů B-buněk; lidé středního věku; Transfection; malá interferující RNA; Receptors, Antigen, B-Cell; Oligonucleotide Array Sequence Analysis; dospělí; Female; Aged; regulace genové exprese u leukemie; RNA, Small Interfering; lidé; Male